INFLUENCE OF SULFUR FUMIGATION ON VOLATILE OIL CONSTITUENTS OF CODONOPSIS RADIX (DANGSHEN) BY GC-MS METHOD - Ma, Xiao-qing; Li, Su-mei; Chan, Chi Leung; Su, Tao; Cheng, Brian Chi-Yan; Li, Wei-dong; Fun Fong, David Wang; Yu, Zhi-ling (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Sulfur fumigation is a kind of the processing methods of Chinese medicinal herbs. It can kill contaminated/parasitical microbes and insects on the herbs and to bleach the herbs. Codonopsis Radix, dried roots of Codonopsis pilosula (Dangshen in Chinese), is one of the herbs commonly processed by sulfur fumigation. This study reports the influence of sulfur fumigation on the chemical constituents of volatile oils of Dangshen.Methods: The volatile oils of air-dried or fumigated Dangshen samples were extracted by water-steam distillation and separated by GC capillary column chromatography. The components in individual volatile oil samples were identified and quantitatively determined by GC-MS.Results: The results showed that forty-five compounds were separated and identified from the volatile oils of Dangshen samples. The contents of 2-octyn-1-ol, phenylethyl alcohol, paeonol and cedrenol in sulfur fumigated Dangshen were much lower than in air-dried Dangshen. On the contrary, the contents of α-lonone, sativene, thujopsene, tetradecanoic acid and methyl cis-9,10-epoxystearate were increased by sulfur fumigation.Conclusions: Sulfur fumigation caused significant changes on the volatile oil constituents of Dangshen samples. Further explorations are necessary to investigate how these chemical changes occurred and whether these changes would affect the efficacy and safety of Dangshen.Key words: Sulfur fumigation; volatile oil; Dangshen; Codonopsis pilosula; GC-MS